Observation of contexts, institutional management and praxis of university research, for a scientific culture in Ecuador (Islas, 2023)
Introduction: In the midst of international historical circumstances that, especially from the 21st century onwards, do not favor the best scientific-editorial practices, this article addresses the problems of a scientific culture in Ecuador, based on the contexts, institutional management, and praxis of university research.Methods: The work is conducted within academic anthropology, using participant observation, having established a reference point of good practices. It incorporates autoethnography and professional testimony as additional sources of knowledge.Results: Among others, issues such as institutional bureaucratization contrary to science, fragmented thinking, an anomalous imaginary of research praxis, subversion of current scientific communication formats, and the emergence of predatory tutors are identified and described.Conclusions: Ecuador demonstrates a functional inexperience in research, which affects a scientific culture that has not yet systematized good academic practices.
Keywords: Ecuador; University; bureaucracy; scientific research; research management; functional inexperience